Competitive Recovery–Stress and Mood States in Mexican Youth Athletes - Reynoso-Sánchez, Luis Felipe; Pérez-Verduzco, Germán; Celestino-Sánchez, Miguel Ángel; López-Walle, Jeanette M.; Zamarripa, Jorge; Rangel-Colmenero, Blanca Rocío; Muñoz-Helú, Hussein; Hernández-Cruz, Germán (Frontiers in Psychology, 2021)
Background: Monitor recovery-stress balance in sport is becoming more relevant to prevent training maladaptation and reach the optimal performance for each athlete. The use of questionnaires that identify the athlete's recovery-stress state have much acceptance in sports due to reliability and useful, furthermore for its low cost. Identify possible differences between sport modalities and gender is important to determine specific needs and possible intervention ways to keep a recovery-stress balance. The aim was to analyze the differences in the recovery-stress state and mood states by gender and sport type during the competitive phase in young Mexican athletes. As a secondary objective, it was analyzed the psychometric properties of the Mexican version of the Recovery-Stress Questionnaire for Athletes (RESTQ-Sport). Methods: A cross-sectional study was carried on with 461 athletes (61% women and 39% men), 17.95 (±1.2) years-old from six sports disciplines participated in the study. The RESTQ-Sport and Profile of Mood States (POMS) were applied in a single moment. Differences by sex and sports modality were analyzed. RESTQ-Sport’s confirmatory factor analysis was performed following the stress and recovery theoretical structure of two stress (general and sport) and two recovery (general and sport) dimensions, at last, the concurrent validation with the POMS was carried on. Results: Significant differences by sex were found in General Recovery and Sport Stress dimensions of the RESTQ-Sport as well as, Vigor factor of the POMS, being higher for men; furthermore, both Sport Recovery dimension of RESTQ-Sport and Cholera, Fatigue and Depression factors from POMS also had differences by sport type, showing a less recovery and high stress for individual sport athletes. Goodness-of-fit indexes of the model for the RESTQ-Sport were acceptable. Pearson's correlation between questionnaires was moderate (p < .05). Conclusion: The recovery-stress state show differences in function of gender and sport modality. More special attention is suggested for women and individual sport athletes. The higher punctuation for men compared to women in sport stress dimension did not negatively affect the recovery-stress balance for males’ athletes. Finally, the Mexican context adaptation of the RESTQ-Sport provides a psychometric instrument suitable to assess the recovery-stress balance in Mexican athletes.